2019
DOI: 10.3390/atmos10120731
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Microscale Wind Simulations with a Coupled WRF–CFD Model in the Chongli Mountain Region of Hebei Province, China

Abstract: To ensure successful hosting of the 2022 Olympic Winter Games, a comprehensive understanding of the wind field characteristics in the Chongli Mountain region is essential. The purpose of this research was to accurately simulate the microscale wind in the Chongli Mountain region. Coupling the Weather Research and Forecasting (WRF) model with a computational fluid dynamics (CFD) model is a method for simulating the microscale wind field over complex terrain. The performance of the WRF-CFD model in the Chongli Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…e evaluation of wind speed against measurements from tower and UAS data showed that this coupling was able to simulate reasonably various flow micro features. Similar results are found in [24] who used the one-way offline coupling system to simulate wind fields in the Chough Mountain in China. Reference [18] coupled the CFD software OpenFOAM with the WRF model to investigate the atmospheric boundary layer structure, ambient wind, and pollutant dispersion within the built-up areas of Shenyang, China, and found that the OpenFOAM simulation driven by the mesoscale WRF simulation is a reliable method to understand the complex flows and dispersion around buildings.…”
Section: Introductionsupporting
confidence: 80%
“…e evaluation of wind speed against measurements from tower and UAS data showed that this coupling was able to simulate reasonably various flow micro features. Similar results are found in [24] who used the one-way offline coupling system to simulate wind fields in the Chough Mountain in China. Reference [18] coupled the CFD software OpenFOAM with the WRF model to investigate the atmospheric boundary layer structure, ambient wind, and pollutant dispersion within the built-up areas of Shenyang, China, and found that the OpenFOAM simulation driven by the mesoscale WRF simulation is a reliable method to understand the complex flows and dispersion around buildings.…”
Section: Introductionsupporting
confidence: 80%
“…STAR-CCM+ solves the RANS equations with the realizable k-ε turbulence closure scheme in this study (Lei et al, 2004;L. Li et al, 2006;S. Li et al, 2019).…”
Section: Physical Model and Boundary Conditionsmentioning
confidence: 99%
“…In order to save computing resources, the RANS turbulence model with realizable 140 k-ε is used in this study (Li et al, 2019;Li et al, 2006;Lei et al, 2004). The governing equations (1-3) of CFD are as follows:…”
Section: Physical Model and Boundary Conditionsmentioning
confidence: 99%